2004
DOI: 10.1021/ja0464802
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine as A Robust Anchor to Immobilize Functional Molecules on the Iron Oxide Shell of Magnetic Nanoparticles

Abstract: We report on the use of dopamine (DA) as a robust molecular anchor to link functional molecules to the iron oxide shell of magnetic nanoparticles. Using nitrilotriacetic acid (NTA) as the functional molecule, we created a system with an M/Fe2O3-DA-NTA (M = Co or SmCo5.2) nanostructure, which possesses high stability and specificity for separating histidine-tagged proteins. The well-established biocompatibility of iron oxide and the robust covalent bonds between DA and Fe2O3 render this strategy attractive for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
649
0
7

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 859 publications
(666 citation statements)
references
References 27 publications
10
649
0
7
Order By: Relevance
“…To conjugate PEG to particles, different anchoring groups such as silane, 11,12 dopamine, 13 phosphate, 14 nitrodopamine, 15 and multidentate catechol have been already utilized. 16 Xie et al transferred and stabilized oleic acid/oleylamine coated NPs by PEG-dopamine and demonstrated a remarkable reduction in non-specific uptake by macrophage cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To conjugate PEG to particles, different anchoring groups such as silane, 11,12 dopamine, 13 phosphate, 14 nitrodopamine, 15 and multidentate catechol have been already utilized. 16 Xie et al transferred and stabilized oleic acid/oleylamine coated NPs by PEG-dopamine and demonstrated a remarkable reduction in non-specific uptake by macrophage cells.…”
Section: Introductionmentioning
confidence: 99%
“…18 To date, a handful of studies has shown the capability of PEG for stabilization of small iron oxide NPs (d core ≈ 10 nm). [13][14][15]17,18 Nonetheless, the feasibility of transferring larger iron oxide NPs (d core ≈ 25 nm) with PEG and their further functionalization for biomedical implications have not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22] Different from these previous functionalization steps, our approach is to conjugate biotinylated NLS to monodisperse Fe 3 O 4 nanoparticles through NeutrAvidin (NAv) and a surfactant combination of polyethylene glycol (PEG) and dopamine (DPA), or 4-(2-aminoethyl)benzene-1,2-diol. DPA can form a strong chelate chemical bond with the iron oxide surface, [23,24] and PEG has been used widely to protect nanoparticles for their stabilization under physiological conditions. [25,26] …”
Section: Introductionmentioning
confidence: 99%
“…Magnetic©nanoparticles©have©been©extensively©ap-plied©in©chemistry,©biochemistry,©biology,©and©medi-cine,© such© as© drug© carriers,© bioseparation,© sensors,© and enzyme©immobilization© [25][26][27][28]©because©of©the©great convenience© of© operations© by© applying© a© magnetic© field and© along© with© the© distinct© features© resulting© from© the high© surface-to-volume© ratio© [29].© In© phosphoproteome, Address© reprint© requests© to© Dr…”
mentioning
confidence: 99%
“…Magnetic©nanoparticles©have©been©extensively©ap-plied©in©chemistry,©biochemistry,©biology,©and©medi-cine,© such© as© drug© carriers,© bioseparation,© sensors,© and enzyme©immobilization© [25][26][27][28]©because©of©the©great convenience© of© operations© by© applying© a© magnetic© field and© along© with© the© distinct© features© resulting© from© the high© surface-to-volume© ratio© [29].© In© phosphoproteome, the magnetic nanoparticles have been implemented for the selective capture and/or enrichment of phosphopeptides from the complex proteolytic digests by using the metal affinity technique for mass spectrometry. For example, Chen et al [17,18] used the TiO 2 and ZrO 2 -coated iron oxide magnetic nanoparticles as the effective affinity probes for the selective concentration of phosphopeptides from the tryptic protein digests in MALDI-TOF MS with a low-femtomole limit of detection; Tan et al [30] directly employed the TiO 2 -modified magnetic nanoparticles on MALDI targets, which was also demonstrated the specific capture and confident detection of phosphopeptides in MALDI-TOF-MS.…”
mentioning
confidence: 99%